Decomposition and nutrient release of sal leaf litter as influenced by legume leaf litter of the sal forests - Sultana, Tania; Hossain, Mohammad Zabed; Ahmed, Ashfaque; Hoque, Sirajul (Dhaka University Journal of Biological Sciences, 2013)
Abstract not available Dhaka Univ. J. Biol. Sci. 22(2): 183-186, 2013 (July)